2007
DOI: 10.1371/journal.pone.0000968
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of a Leprosy Immunotherapeutic Bacillus Provides Insights into Mycobacterium Evolution

Abstract: BackgroundEvolutionary dynamics plays a central role in facilitating the mechanisms of species divergence among pathogenic and saprophytic mycobacteria. The ability of mycobacteria to colonize hosts, to proliferate and to cause diseases has evolved due to its predisposition to various evolutionary forces acting over a period of time. Mycobacterium indicus pranii (MIP), a taxonomically unknown ‘generalist’ mycobacterium, acts as an immunotherapeutic against leprosy and is approved for use as a vaccine against i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…This hypothesis agrees with the current model for the evolution of mycobacteria, which postulates that the ancestor of mycobacteria was an environmental organism living in an aquatic habitat [50]. Recent genome analysis of the environmental Mycobacterium indicus pranii , a member of the M. avium complex, further supports this hypothesis in which the most recent common ancestor of mycobacteria gave rise to waterborne M. marinum and M. ulcerans on one branch, the M. avium complex on a second branch and the M. tuberculosis complex on a third branch [50].…”
Section: Discussionsupporting
confidence: 91%
“…This hypothesis agrees with the current model for the evolution of mycobacteria, which postulates that the ancestor of mycobacteria was an environmental organism living in an aquatic habitat [50]. Recent genome analysis of the environmental Mycobacterium indicus pranii , a member of the M. avium complex, further supports this hypothesis in which the most recent common ancestor of mycobacteria gave rise to waterborne M. marinum and M. ulcerans on one branch, the M. avium complex on a second branch and the M. tuberculosis complex on a third branch [50].…”
Section: Discussionsupporting
confidence: 91%
“…It has been often commented that mycobacteria have a distinctive and complex ecology; some species or strains are specialists, some are generalists and others may be neither specialist nor generalist in their lifestyle (Ahmed et al ., ). Whereas Mycobacterium is a genus of mesophilic species based on the conditions required for optimum growth, our data suggest that certain mycobacteria are as resilient to key solute‐induced stresses as some of the most stress‐tolerant microbes known to science.…”
Section: Discussionmentioning
confidence: 97%
“…Mycobacteria are mycolic acid‐containing, high guanine‐cytosine‐content bacterial organisms belonging to the Actinobacteria phylum [1]. Comparative genomics indicated that the most recent common ancestor of Mycobacteria was an environmental species [2,3] which evolved towards soil‐borne mycobacteria, waterborne mycobacteria such as Mycobacterium avium , Mycobacterium intracellulare, and host‐associated species including M. avium subsp. paratuberculosis and Mycobacterium avium subsp.…”
Section: Mycobacteria Evolved From An Environmental Ancestormentioning
confidence: 99%